A methodology to estimate wave‐induced coastal flooding hazard maps in Spain. Issue 3 (12th August 2015) - Tomás, A.; Méndez, F.J.; Medina, R.; Jaime, F.F.; Higuera, P.; Lara, J.L.; Ortiz, M.D.; Álvarez de Eulate, M.F.
Abstract: The purpose of the European Flooding Directive (2007/60/CE) is to establish a European framework for the assessment and management of flood risks. The aim is to reduce the adverse flooding consequences on a wide range of topics such as human health, environmental and cultural heritage, and economic activity. In Spain, coastal zone flood hazard and risk maps are managed by the Environment Spanish Ministry (MAGRAMA, D irección   G eneral para la   S ostenibilidad de la   C osta y el   M ar ). These maps are designed using the methodology explained in this paper. This methodology allows to perform quick flood hazard maps along the Spanish coast because of the combination of high‐resolution marine climate databases, state‐of‐the‐art numerical models, innovative data‐mining techniques and statistical models.